Project management for engineering and construction - Oberlender, Garold D. (Boston : McGraw-Hill, 2000)
This book presents the principles and techniques of managing engineering and construction projects from the conceptual phase, through design and construction, to completion.
Keywords: Management; Engineering; Engineering -- Management